Functional consequences of the human DMT1 (SLC11A2) mutation on protein expression and iron uptake - Priwitzerova, Monika; Nie, Guangjun; Sheftel, Alex D; Pospisilova, Dagmar; Divoky, Vladimir; Ponka, Prem (Blood, 2005)
We have previously described a case of severe hypochromic microcytic anemia caused by a homozygous mutation in the divalent metal transporter 1 (DMT1 1285G > C). This mutation encodes for an amino acid substitution (E399D) and causes preferential skipping of exon 12 during processing of the DMT1 mRNA. To examine the functional consequences of this mutation, full-length DMT1 transcript with the patient's point mutation or a DMT1 transcript with exon 12 deleted was expressed in Chinese hamster ovary (CHO) cells. Our results demonstrate that the E399D substitution has no effect on protein expression and function. In contrast, deletion of exon 12 led to a decreased expression of the protein and disruption of its subcellular localization and iron uptake activity. We hypothesize that the residual protein in hematopoietic cells represents the functional E399D DMT1 variant, but because of its quantitative reduction, the iron uptake activity of DMT1 in the patient's erythroid cells is severely suppressed.
Keywords: železo; fluorescenční protilátková technika; CHO buňky; křečci praví; proteiny přenášející kationty; Humans; Iron; Cation Transport Proteins; Female; Anemia, Hypochromic; Blotting, Western; lidé; zvířata; CHO Cells; transfekce; ženské pohlaví; bodová mutace; Male; proteiny vázající železo; Iron-Binding Proteins; Point Mutation; Cricetinae; Transfection; Fluorescent Antibody Technique; Animals; western blotting; mužské pohlaví; hypochromní anemie